PENERAPAN EXCELLENT SERVICE DALAM PENINGKATAN MANAJEMEN PELAYANAN KEIMIGRASIAN: THE IMPLEMENTATION OF EXCELLENT SERVICE IN ENHANCING IMMIGRATION SERVICES MANAGEMENT - Yosua Hernando Martua Samosir; Agung Sulistyo Purnomo (Polteknik Imigrasi, 2025)
Excellent service in immigration administration has become an urgent necessity in line with the increasing public expectations for high-quality public services. This study aims to analyze the implementation of the excellent service concept within Indonesia’s immigration services, identify supporting and inhibiting factors, and formulate strategies to enhance service quality. Using a qualitative approach through literature review, the study finds that excellent service implementation is supported by service digitalization, improvement of human resource competencies, and transformation of organizational culture within the Directorate General of Immigration. Nevertheless, challenges such as infrastructure disparities, uneven human resource quality, and resistance to change remain significant obstacles. This research recommends continuous human resource training, expansion of digital services across all regions, and increased community participation in service evaluations. Through these strategies, immigration services are expected to deliver superior, responsive, and equitable public service experiences across Indonesia.